Brasileiros imigrantes na Europa: das representações sociais aos processos identitários - Batista, Roberta Rangel (2014)
The Brazilian immigration to Europe was reinforced based on believes that the European countries would contribute for a change in migrants’ status, especially with better financial and living conditions. Despite the European economic crises, this territory still remains as a sociability model. Referenced in the junction of social representation theory and social identity theory, the aim of this research was to analyze the Brazilian immigrants identity processes’ based on the investigation of immigration’s social representations. The six countries with the highest number of Brazilians in Europe, according to the Brazilian Foreign Relations Ministry, were chosen for the research development: Great Britain, Portugal, Spain, Italy, Germany and France. The investigation was formulated in the composing of three studies: (S1) documentary analysis that intended to know the immigration and immigrants social representations, broadcasted at the newspapers, in the six countries chosen; (S2) social representation research of the objects Brazil, Europe, Brazilians, European and immigrants and the metarepresentations of Brazilians and immigrants to 180 Brazilians living at the six territories; and (S3) aimed to analyze the identity processes of Brazilian immigrants in Great Britain considering their immigration experiences. The corpora of data were analyzed using the software ALCESTE and EVOC as well as the phenomenological method in psychological research, according to the research objectives and nature of the data. The results support that the social representation of the objects immigration and immigrants, broadcasted by the European newspapers, are based in meanings such as illegality, criminality and violence against migrants, reflecting the group image as a social problem, threatening and strange to the society. Among the Brazilian immigrants, as a representations’ subjects, the meanings associated to the territories Brazil and Europe, indicated that, despite the affective elements referred to the country of birth, the culture and life quality, indicate that Europe is a better territory to live in. From the territories to the social groups, the European and Brazilian were represented with mostly positives elements: the first group was seen as more reserved and polite, and the second one, with elements related to a meaning that reflects a happy image and Brazilian’s receptivity. The Brazilians metarepresentation is associated with themes 24 such as sexuality (sex and prostitution) and festivities (carnival and samba). At the representation field related to immigrant, positive (brave, opportunity and fighter) and negative (prejudice and difficulties) elements were declared, noting that this last dimension is the most prominent one in association with the metarepresenations of the same object (steal jobs and opportunists). The Brazilian’s immigration experience, on the other hand, reflect that, although there is an identification with the European group, mainly due to marriage relations and cultural conditions offered by the European country, all the Brazilians declare their belonging to the Brazilian and to the immigrant group. The discussion is supported on the fact that the hegemonic social representations, about the immigrants, were based in a dominant ideology that judges the group in a depositary category and distinguish it as an unknown, strange, threatening and unfamiliar group to the European societies. In contrast, the Brazilian immigrants express controversial social representations that resist the negative image placed by the reference group. This underlying dynamics are demonstrated at the Brazilian immigrants social identity processes’, that allows them to transit between the different groups in order to gather the elements needed to compose and maintain their positive self-image.